Electrical impedance myography changes after incomplete cervical spinal cord injury: An examination of hand muscles. Issue 11 (November 2017) - Li, Le; Shin, Henry; Stampas, Argyrios; Li, Xiaoyan; Zhou, Ping
Highlights: Electrical impedance myography (EIM) was applied to examine hand muscles after spinal cord injury (SCI). SCI may result in lower reactance, phase angle, and altered anisotropy compared to healthy control. This can be due to membrane integrity alteration, fat infiltration, and muscle structural changes. Abstract: Objective: This study was to apply the newly developed electrical impedance myography (EIM) technique to examine hand muscles in patients with an incomplete cervical spinal cord injury (SCI). Methods: EIM was performed on the thenar, hypothenar, and first dorsal interosseous (FDI) muscles of SCI ( n  = 16) and age-matched healthy control ( n  = 18) subjects. By sending low intensity and high frequency current through the skin and measuring the consequent voltage, EIM estimates the major impedance parameters, which include resistance ( R ), reactance ( X ) and phase angle ( θ ). Results: The SCI group had lower reactance and phase angle ( p  < 0.0001) as compared to the control group in all three muscles, and lower resistance in the thenar muscle ( p  < 0.05). The SCI group also demonstrated a smaller anisotropy in resistance ( p  < 0.0001) and larger anisotropy in phase angle ( p  < 0.05) compared to those from healthy controls. Conclusion: The reduced reactance and phase angle of paralyzed muscles could be due to changes of membrane integrity and fat infiltration, whereas the change in the anisotropy may reflect the rearrangement of muscle fiber geometry. Significance: The EIM provides a quick and convenient tool for examination of muscle alterations after SCI.